DETERMINANTS OF JOB SATISFACTION AND EMPLOYEE PERFORMANCE IN INFORMAL EDUCATION INSTITUTIONS: A STUDY IN PARE ENGLISH VILLAGE, KEDIRI, CENTRAL JAVA, INDONESIA - Endang Saefuddin Mubarok; Syahrullah, Rudi Salam (Current Journal of Human Resource Management (CJHM), 2023)
The demand for English language proficiency has led to the growth of informal education institutions in Indonesia. This research aims to examine the determinants of job satisfaction and employee performance in Pare English Village, Kediri, Central Java, Indonesia. The study collects and analyzes data related to motivation, organizational commitment, financial compensation, internal communication, work satisfaction, and employee performance to provide practical benefits for managing business organizations. A descriptive and explanatorily-quantitative method was employed, including samples of 60 persons, questionnaires, and Structural Equation Modeling (SEM) data analysis. The research demonstrates that motivation influences job satisfaction, financial compensation impacts employee performance, and organizational commitment affects both job satisfaction and performance. Internal communication is found to significantly affect job satisfaction, while job satisfaction significantly influences employee performance. The strength of the dependent variables indicates a significant multiple correlation squared (R2) value. The results underscore the importance of understanding the determinants of job satisfaction and employee performance in informal education institutions to improve management practices